Sinn und Zweck kurzer Freiheitsstrafen: Die Reformbedürftigkeit der Ersatzfreiheitsstrafe - Mehlich, Andreas, LL.M. (Tectum Verlag, 2024)
Imprisonment for failure to pay a fine (the alternative sentence) is the enfant terrible of the German sanctions law. Introduced as a means of exerting pressure to ensure that fines are paid, its enforcement has a socially damaging effect, particularly on deprived offenders. This is a dilemma, because it results in people being imprisoned after all, for offences that the courts did not deem imprisonable.Real alternatives are therefore needed to avoid and reduce the enforcement of alternative custodial sentences. What is needed is a concept in which community service is designed as a first-priority alternative that is also flexible and appropriate in individual cases. A concrete offer of work sent with the summons to commence imprisonment can be helpful here - in contrast to the existing application requirement.